2006
DOI: 10.1165/rcmb.2005-0256oc
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glycosaminoglycans in Human Airway Secretions

Abstract: Glycosaminoglycans (GAGs), known to be present in airway mucus, are macromolecules with a variety of structural and biological functions. In the present work, we used fluorophore-assisted carbohydrate electrophoresis (FACE) to identify and relatively quantify GAGs in human tracheal aspirates (HTA) obtained from healthy volunteers. Primary cultures of normal human bronchial epithelial (NHBE) and submucosal gland (SMG) cells were used to assess their differential contribution to GAGs in mucus. Distribution was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 48 publications
4
57
0
2
Order By: Relevance
“…These results are in agreement with the reported presence of heparin, chondroitin and DS in tracheal tissue sections [9] and of HA in the human lung [11][12][13]. However, we observed that total GAG synthesis was reduced in ASMC from asthma and COPD patients when compared with controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the reported presence of heparin, chondroitin and DS in tracheal tissue sections [9] and of HA in the human lung [11][12][13]. However, we observed that total GAG synthesis was reduced in ASMC from asthma and COPD patients when compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…The function of these GAG varies within the organ in which they are located. In the human lung, KS was found on the apical surface of ciliated epithelial cells, CS and DS were secreted by epithelial and submucosa gland cells, and HS was reported in the ECM of tracheal tissue sections [9]. HA and the enzymes that metabolise it are also endogenous to the pulmonary environment, and HA has been isolated from the lungs of mammals (sheep, guinea pig and rat) [10], and human lung parenchyma and pleura [11].…”
mentioning
confidence: 99%
“…Supernatants were precipitated with ethanol, freeze-dried and prepared for the assessment of HA amounts by fluorophore-assisted carbohydrate electrophoresis (FACE) analysis as previously described (16,42) or HA size as described below.…”
Section: Ha Contentmentioning
confidence: 99%
“…It is released by submucosal glands and by superficial airway epithelial cells (16,17) where it serves as an anchor for secreted proteins involved in host defense, preventing their removal by mucociliary clearance (18 -20). Tissue kallikrein (TK), a serine protease involved in airway inflammation and mucus hypersecretion (15,21) is bound to, and inhibited by HMWHA at the airway epithelial surface.…”
mentioning
confidence: 99%
“…Endogenous HMW HA plays a pivotal role in the homeostasis of the upper and the lower airways: it is an important component of the normal airway secretions, exerts anti-inflammatory and antiangiogenic actions, promotes cell survival and mucociliary clearance, organizes extracellular matrix, stabilizes connective tissues, sustains healing processes and regulates tissues hydration [144,[232][233][234]. Hence, exogenous HMW HA represents a promising therapeutic agent for the treatment of nasal and lung diseases that involve inflammation, oxidative stress and epithelial remodeling, such as allergic and non-allergic rhinitis, asthma, chronic obstructive pulmonary disease and cystic fibrosis [143,233,[235][236][237][238].…”
Section: Rhinology and Pneumologymentioning
confidence: 99%